PENYANDIAN CITRA MENGGUNAKAN ALGORITMA 4D PLAYFAIR CIPHER DENGAN PEMBANGKITAN KUNCI MODIFIKASI LINEAR FEEDBACK SHIFT REGISTER - Rahayu, Rivi Tri; Riski, Abduh; Kamsyakawuni, Ahmad (Jurusan Matematika FMIPA Universitas Jember, 2019)
The fast development of sophisticated technology make it easier for someone to send a message to other but can also make it easier for third parties to sabotage the content of the message, so a technique called cryptography is needed to secure the message. Image encoding is one of the techniques for securing messages in cryptography. In enhancing security in image encoding, this study discusses about Playfair Cipher, 3D Playfair Cipher and 4D Playfair Cipher with key generation using LFSR Modification. The encryption process using 4D Playfair Cipher with key generation using LFSR Modification visually produces cipher image that is different from the original image compared to using Playfair Cipher and 3D Playfair Cipher. In the decryption process using Playfair Cipher, 3D Playfair Cipher and 4D Playfair Cipher-Modification LFSR can return cipher image to its original image. The result of the study shows that the proposed method can be used to secure the message. Keywords: Playfair Cipher, 3D Playfair Cipher, 4D Playfair Cipher, LFSR